Akuntansi Komitmen dan Kontijensi Bank dan Akuntansi Jasa Lainnya - Angerlo; Illya Firna Febriyanti; Leony Fenanda; Stevani Thoe; Triyana (Politeknik Raflesia Press, 2025)
This study examines how commitment and contingent accounting, as well as auxiliary banking services, influence internal control effectiveness within banking institutions. Using a qualitative descriptive approach, this research analyzes the impact of accounting treatments for bank commitments, contingencies, and other services (money transfer, payment point, safe deposit box, and Rupiah travellers cheques) on internal control quality. Findings suggest that proper classification and recognition of commitments and contingencies, combined with well-regulated auxiliary services, enhance accountability and reduce operational risk. The study provides insight into practical internal control implementation, especially under PSAK 57 regarding provisions and contingent liabilities.